TRAUMA AND THE DIVIDED SELF IN JONATHAN SAFRAN FOER’S EXTREMELY LOUD AND INCREDIBLY CLOSE - Sabrina Sakha Andien; Prayudias Margawati (Lire Journal (Journal of Linguistics and Literature), 2026)
In post-9/11 fiction, trauma is often represented not merely as a psychological condition but as a narrative disruption that fragments the protagonist's sense of self. This article examines the representation of the divided self in Jonathan Safran Foer’s novel Extremely Loud and Incredibly Close through the lens of R.D. Laing’s theory of the Divided Self. This study uses a descriptive qualitative approach to examine how self-fragmentation and the construction of a false-self system dramatize the protagonist’s inner conflict. The findings indicate that narrative elements, such as rigid communication patterns and the deployment of humor, function as a false-self system that serves as a defense mechanism against ontological insecurity. This study argues that the tragedy of 9/11 triggered a sharp separation between the inner self and the false self. Ultimately, the trauma in this novel manifests as a catalyst for a divided self that alienates inner feelings from their social representation, thereby trapping the protagonist in self-isolation.